Utilization of Beauveria Bassiana in Controlling Cocoa Pod Borer (Conopomorpha Cramerella) Pests (International Journal of Scientific Research in Science and Technology, 2025)
One of the factors that causes the decline in cocoa plant production is the attack of cocoa pod borer pests (Conopomorpha cramerella Snellen). To suppress the attack of cocoa pod borer pests, biological agents are used, namely by using entomopathogenic microbes Beauveria bassiana. This study aims to determine the best concentration of Beauveria bassiana utilization in controlling Cocoa Pod Borer Pests (Conopomorpha cramerella). The research method used a completely randomized design (CRD) with 4 treatments, namely Po: Control, P1 Beauveria bassiana with concentration 10-5, P2 Beauveria bassiana with concentration 10-6 and P3: Beauveria bassiana with concentration 10-7. Observation parameters are the time of emergence of spores in cocoa pod borer larvae (incubation period) in the observation interval of 1 day after application. Time of death of cocoa pod borer larvae, Percentage of cocoa pod borer larval mortality (%). The results of the study showed that the entomopathogenic Beauveria bassiana was able to control the larvae of the cocoa pod borer pest (Conopomorpha cramerella Snellen) and the best concentration of Beauveria bassiana utilization in controlling the cocoa pod borer pest (Conopomorpha cramerella Snellen) was at a concentration 10-7
Keywords: cocoa; pest; Beauveria; entomopathogenic